Stenelmis koreana Satô, 1978 (Coleoptera: Elmidae): confirmed as a wide-spread species by DNA-sequencing - Litovkin, Stanislav V.; Bruvo-Mađarić, Branka; Jäch, Manfred A.; Jung, Sang Woo; Efimov, Dmitry A. (Zootaxa, 2019)
Stenelmis koreana Satô, 1978 (Coleoptera: Elmidae) is here recorded for the first time from Kyrgyzstan and Western Siberia. It was hitherto thought to be confined to Korea and the Russian Far East. The identification of a specimen from Kyrgyzstan was confirmed by DNA-sequencing after comparison with two sequences of S. koreana from Korea. The COI haplotype of the Kyrgyzstan specimen has very low sequence divergence (0.53 % or 0.0053 uncorrected p-distance) with respect to the sequences of the Korean specimens, which is within the standard intraspecific sequence divergence for COI in beetles.